Impact of E-Learning on Learning Mandarin in Elementary Schools During Covid-19 - Yi Ying; Paulina Paulina; Yorika Rovemia Mulyadani; Krystl Marie O. Lim (Bina Nusantara University, 2021)
In the teaching and learning process, the roles of teachers and students will be balanced if there is good communication between them. However, learning methods from face-to-face to e-learning suddenly prompt the teachers to look for various alternatives to convey the material due to COVID-19 pandemic. The research analyzes the impact of COVID-19 on the learning process, especially Mandarin, in an elementary school. The research uses a descriptive-analytical method with questionnaires. The questionnaires are filled out by 34 students from the fifth grade in Bina Kusuma Elementary School, Jakarta. The research finds the positive impacts of elearning in the school regarding Mandarin learning. First, the subject is more interesting and easier to understand. Second, students can learn the right notes and pronunciation independently. Third, using WhatsApp and Zoom can help students recall previously learned vocabulary. Fourth, students can learn new vocabulary independently. Fifth, e-learning can motivate students to learn and gain experience from new learning methods. Sixth, students can manage their time in learning, so they become more independent. Last, students can study anywhere and anytime without time and space limits. However, the weakness of e-learning is the speed of the internet. It affects the students in obtaining the provided subject by the teachers.